On The Eneström-Kakeya Theorem - Liman, A; Rasool, Tawheeda; Shah, WM (BIBECHANA, 2013)
In this paper we present some interesting generalizations of Eneström-Kakeya type results concerning the location of zeros of a polynomial in the complex plane. We relax the hypothesis and put less restrictive conditions on the coefficients of the polynomial, and thereby generalize some classical results. DOI: http://dx.doi.org/10.3126/bibechana.v10i0.8067 BIBECHANA 10 (2014) 71-81